1986
DOI: 10.1007/bf02374293
|View full text |Cite
|
Sign up to set email alerts
|

Growth, development and yield of pawpaw (Carica papaya L.) ‘Homestead selection’ in response to soil moisture stress

Abstract: The effects of four soil water potential regimes under greenhouse conditions on growth, development, and yield of 'Homestead selection' pawpaw were investigated. The objectives were to determine the critical soil water potential regime and the moisture sensitive stages of growth of pawpaw. Repeated cycles of stress to -6.0 bar soil water potential imposed as from vegetative phase prevented fruit formation by constantly causing flower abscission. The stressed plants were stunted in size. The -2.0 bar soil water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 3 publications
1
6
0
4
Order By: Relevance
“…Even though the difference was small, T5 had the greatest crown diameters, during the entire evaluation period, having practically the same thermal units as T3, in the vicinity of 3,000°C d. Thus, in general papaya trees tend to reduce their crown diameters with time; however, the values verified in this work seem to be related to the lack of soil water (T1), which was also verified by Aiyelaagbe et al (1986), and to the low winter temperatures influencing all evaluated treatments, a condition also found by Silva (1999). No other reductions were detected.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Even though the difference was small, T5 had the greatest crown diameters, during the entire evaluation period, having practically the same thermal units as T3, in the vicinity of 3,000°C d. Thus, in general papaya trees tend to reduce their crown diameters with time; however, the values verified in this work seem to be related to the lack of soil water (T1), which was also verified by Aiyelaagbe et al (1986), and to the low winter temperatures influencing all evaluated treatments, a condition also found by Silva (1999). No other reductions were detected.…”
Section: Resultssupporting
confidence: 72%
“…The estimated regressions did not present sufficiently high coefficients of determination, demonstrating that they do little to explain the data obtained, despite the observed significance. This could probably be related to the fact that in studies conducted by Aiyelaagbe et al (1986) and Awada et al (1979), while studying water stress in papaya trees, found that the no. of leaves of plants submitted to water stress decreases only due to leaf abcission and not because of the number of emitted leaves, since the numbers of nodes in the plants were the same, and only the distance between nodes was different, under the different moisture regimes.…”
Section: Resultsmentioning
confidence: 98%
“…Tabela 5. Valores totais da lâmina aplicada (ETr), da evapotranspiração máxima da cultura (ETm), do déficit de evapotranspiração relativa (1 -ETr/ETm), da produção real comercial (Yrc), da produção máxima comercial (Ymc) e da queda de rendimento relativo (1 -Yrc/Ymc) nos diversos tratamentos realizados na cultura do mamoeiro Híbrido UENF/ CALIMAN01 Alguns pesquisadores, como Awada (1961), Awada et al (1979) e Aiyelaagbe et al (1986) afirmam que, em relação à produção comercial, o mamoeiro é muito sensível ao défi-cit de umidade no solo. Silva (1999) e Awada et al (1979) observaram, em relação à lâmina de água aplicada, que o incremento da produtividade total foi menor que o da produtividade comercial.…”
Section: Methodsunclassified
“…The dominant species such as M. indica were planted mainly for fruits, shade and windbreaks during storms to protect the housing units. Carica papaya and Psidium guajava produces fruits within short period within one and three years respectively, in addition to short gestation, the soil in Choba Park is well drained sandy soil suitable for such species (Aiyelaagbe et al, 1986). Pawpaw is one of the most nutritious fruit grown and consumed in Nigeria; it produces fruit throughout the year on good soil.…”
Section: Journal Of Environment and Ecologymentioning
confidence: 99%